Effect of Sacubitril/Valsartan on Reducing the Risk of Arrhythmia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Ruxin; Ye, Haowen; Ma, Li; Wei, Jinjing; Wang, Ying; Zhang, Xiaofang; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Background And Objective: Relevant data of several large clinical studies on sacubitril/valsartan (SV) shows that it may have an additional effect on reducing the risk of arrhythmia compared with angiotensin converting enzyme inhibitor (ACEI)/angiotensin receptor inhibitor (ARB), but current results are inconsistent. Here, we conduct a meta-analysis of related randomized controlled trial (RCT) to evaluate the protective effect of SV on reducing the risk of arrhythmia. Methods and Results: PUBMED, EMBASE, ClinicalTrials.gov and Cochrane Library were searched for RCTs that treat patients with SV and ACEI/ARB. The results were extracted from each individual study, expressed as binary risk, 95% confidence interval (CI) and relative risk (RR). 16 RCTs met the study criteria, including 22,563 patients. Compared with ACEI/ARB, SV reduced the risk of various arrhythmias (RR 0.87, 95% CI 0.74-1.01, p=0.07), malignant arrhythmias (RR 0.81, 95% CI 0.64-1.03, p=0.09), atrial arrhythmias (RR 0.98, 95% CI 0.83-1.16, p=0.85) and ventricular arrhythmia (RR 0.87, 95% CI 0.70-1.09, p=0.23), but no statistical difference was found, and SV reduced the risk of cardiac arrest (RR 0.52, 95% CI 0.37-0.73, p=0.0002), with statistically significant difference; Subgroup analysis showed that SV increased the risk of atrial fibrillation (Af) (RR 1.06, 95% CI 0.96-1.17, p=0.26), reduced the risk of ventricular fibrillation (VF) (RR 0.85, 95% CI 0.54-1.35, p=0.49) in patients with heart failure (HF), with no statistical difference, SV reduced the risk of ventricular tachycardia (VT) (RR 0.69, 95% CI 0.51-0.92, p=0.01) and malignant arrhythmia (RR 0.83, 95% CI 0.73-0.95, p=0.006) in patients with HF with reduced ejection fraction (HFrEF), with statistical differences. The merged result was robust after sensitivity analysis, and there was no publication bias. Conclusions: Our finding provides evidence that, compared with ACEI/ARB, SV can additionally reduce the risk of most arrhythmias, excluding Af, but it has obvious advantages only in reducing the risks of VT or malignant arrhythmias in patients with HFrEF, and cardiac arrest. The effect of SV on VF is uncertain.